Modern Approaches to The Professional Selection of Specialists of Extreme Profile Based on The Experience of Leading Foreign Countries - Ibragimova Mohinur Sanat qizi (Zien Journals, 2022)
The article analyzes the rich practical experience of psychologists of the Russian Federation, the United States of America and the People's Republic of China in applying various methodsin the process of professional psychological selection of candidates for admission to law enforcement agencies of extreme profile.
Keywords: professional psychological selection; individual psychological characteristics; methodology; candidates